Analisis Manajemen dan Sistem Operasional Lembaga Unit Pengumpul Zakat (UPZ) - BAZNAS di Kabupaten Tulungagung dalam Perspektif Syariah - Ari Pratama, Yoga; Faiqoh, Elok; Agus Alfiyan Nur Ahmada, Muhamad; Huda, Qomarul; Mashudi, Mashudi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to analyze the management and operational system of the Zakat Collection Unit (UPZ) of BAZNAS Tulungagung Regency from a sharia perspective. The UPZ plays a crucial role as an extension of BAZNAS in collecting, distributing, and utilizing zakat funds at the regional level. The research employed a descriptive qualitative method with a literature study approach focusing on institutional analysis and zakat governance based on sharia principles. This approach was chosen because it allows the researcher to explore contextual cause-and-effect relationships and gain a comprehensive understanding of zakat management practices through relevant written sources. Data were obtained from a literature review consisting of ten national and international scientific journals discussing zakat governance, sharia compliance, and Islamic philanthropy management; five major reference books on zakat management and Islamic economics; three official documents from BAZNAS and government regulations, including operational guidelines and annual reports of zakat institutions; and two religious fatwas and sharia guidelines related to zakat fund management and the role of UPZ. The data were analyzed using a descriptive-analytical technique, involving classification, comparison, and synthesis of information from various references to obtain a holistic understanding. The analysis focused on four key aspects: the institutional concept of UPZ, the application of sharia principles in zakat management, the regulatory framework, and the implementation of operational management at the regional level. The findings reveal that structurally, the UPZ of BAZNAS Tulungagung Regency has established an organized management system encompassing planning, implementation, and supervision functions in accordance with BAZNAS guidelines. The application of sharia principles such as trustworthiness (amanah), justice (adl), and accountability has been reflected in the institution’s governance, although challenges remain in terms of transparency, human resource competence, and digital optimization of zakat management systems. This study contributes both conceptually and practically to strengthening sharia-based zakat governance that is professional, transparent, and trustworthy, and it serves as a reference for zakat management institutions in developing effective and accountable zakat systems oriented toward social welfare in line with maqasid al-shariah.